2015 IEEE 23rd International Conference on Network Protocols (ICNP) 2015
DOI: 10.1109/icnp.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Freeing the IP Internet Architecture from Fixed IP Addresses

Abstract: Abstract-The IP Internet architecture is such that applications must bind fixed IP addresses and ports before any other operations can be executed. These early bindings cause bottlenecks, reliability issues, and force applications and protocols to manage complex lower-layer issues. This poses a big challenge to the future of the IP Internet, given the large and growing numbers of nomadic Internet users, the shift in Internet usage from centralized servers to peer-to-peer content sharing, and the popularity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Indeed, part of the justification of recent ICN architectures is the argument that using addresses is inherently limiting in supporting the mobility of services or content. However, as we have argued recently [45], [46], [47], the limitations of prior proposals stem from the assumption that the identifiers used in the communication protocols operating in the data plane must be the same as the identifiers used within the protocol stack of a host or a router to pass information across layers of the stack. We have demonstrated that this does not have to be the case and that indirection within the protocol stack can be done efficiently to allow names and addresses used in communication protocols to differ from the identifiers used inside hosts and router to refer to resources, connections, or remote processes.…”
Section: E Limitations Of Prior Solutionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, part of the justification of recent ICN architectures is the argument that using addresses is inherently limiting in supporting the mobility of services or content. However, as we have argued recently [45], [46], [47], the limitations of prior proposals stem from the assumption that the identifiers used in the communication protocols operating in the data plane must be the same as the identifiers used within the protocol stack of a host or a router to pass information across layers of the stack. We have demonstrated that this does not have to be the case and that indirection within the protocol stack can be done efficiently to allow names and addresses used in communication protocols to differ from the identifiers used inside hosts and router to refer to resources, connections, or remote processes.…”
Section: E Limitations Of Prior Solutionsmentioning
confidence: 97%
“…First, our prior work on "hidden identifiers" in the protocol stack [45], [46], [47] demonstrates that hosts and routers can denote resources, connections and remote processes with identifiers that need not be the same as those used as part of communication protocols. Second, updating the mappings from names to addresses need not be done solely through a common directory service, and indeed communicating hosts or routers can update one another directly if done properly.…”
Section: E Limitations Of Prior Solutionsmentioning
confidence: 99%
“…The use of end-to-end connections between specific end-point addresses prompted the development of many approaches to cope with mobility in the context of the IP Internet [9,33,43,65,82,86,91,93]. However, this prior work does not address eliminating connections for reliable end-to-end communication, and some can be used in NDT.…”
Section: Privacy and Mobility Supportmentioning
confidence: 99%
“…This is an important consideration, especially because the average number of connections that a host has at any given point in time significantly outnumbers the number of separate hosts with which it is communicating, at a ratio of at least 4 to 1! [8] This has profound implications for the scalability of transport-layer solutions. Figure 13 illustrates control message growth for a single handoff as we vary the number of corresponding hosts from 1 to 100.…”
Section: E Control Message Scalabilitymentioning
confidence: 99%
“…In response to the inherent problems with host-identifier proposals, recent host-locator proposals [5], [2], [6], [7], [8] split identifiers from locators above the network layer at end hosts. These approaches propose addressing datagrams to the current network location of a host (i.e., the locator), and updating the IP address bindings made by higher layers (typically at the transport layer) of end hosts by way of additional signaling or protocol options exercised when a host experiences mobility.…”
Section: B Host-locator Approachesmentioning
confidence: 99%